DNAR-09. THE IMPACT OF MISMATCH REPAIR DEFICIENCY ON HIGH GRADE GLIOMAS IN CHILDREN, ADOLESCENTS AND YOUNG ADULTS; A REPORT FROM THE IRRDC AND THE GLIOMA TASKFORCE. (14th November 2022) - Negm, Logine; Nobre, Liana; Bennett, Julie; Chung, Jiil; Fernandez, Nick; Johnson, Monique; Aronson, Melyssa; Zhang, Cindy; Komosa, Martin; Bianchi, Vanessa; Stengs, Lucie; Lim-Fat, Mary Jane; et al.
Abstract: Mismatch repair deficiency (MMRD) is a pan-cancer mechanism resulting in universal hypermutation and aggressive cancers that are resistant to chemoradiation yet sensitive to immunotherapy. MMRD mutations can occur somatically or be inherited as a part of Lynch Syndrome or Constitutional Mismatch Repair Deficiency (CMMRD). Although MMRD affects children, adolescents and young adults (CAYA, ages 0-40) with gliomas, its prevalence and impact of germline inheritance is unknown. Given that high microsatellite instability (MSI) is a key characteristic of MMRD, we previously developed a robust low-coverage whole genome-based tool to quantify MSI, which allows for accurate MMRD detection. We are therefore performing a large-scale MMRD screen of CAYA high grade gliomas (HGGs) and utilizing data from the International Replication Repair Deficiency Consortium (IRRDC) to determine the impact of germline mutations in MMRD gliomas. Ongoing data on 346 HGGs from CAYA patients reveals that MMRD is identified in 6% of HGGs and is not present in tumors with pediatric type alterations. Moreover, of MMRD tumors with IDH1 mutations, none harbor 1p/19q co-deletions. Of patients with available information, all are diagnosed with Lynch Syndrome (69%) or CMMRD (31%), with all Lynch Syndrome diagnoses occurring in patients above 18 years of age. Complementary data from the IRRDC on 113 MMRD patients with gliomas reveal that the median age of glioma is 9.7 and 17.5 years in CMMRD and Lynch Syndrome, respectively (p < 0.001). Strikingly, CMMRD gliomas are enriched for secondary polymerase mutations (60%, p < 0.001) and exhibit ultra-hypermutation, while MMRD gliomas with Lynch Syndrome are enriched for IDH1 mutations (32%, p < 0.025) and harbor a lower mutational burden. Our data reveal a high prevalence of MMRD in CAYA HGGs with alarming impact of germline predisposition. These data can support universal screening for MMRD in high grade glioma diagnostics and identify patients for precision therapeutics.